Communicating Taboos as Conservation Discourse: An Ethnographic Study in Kampung Kuta - Priyo Subekti; Hanny Hafiar; Ibrahim Wada; Susie Perbawasari (UPT Publikasi Ilmiah UNISBA, 2025)
Modernization and tourism pose significant threats to traditional ecological knowledge in many indigenous communities. This study aims to analyze the communication, preservation, and adaptation of pamali, the customary norms that protect Leuweung Gede (the Forbidden Forest) in Kampung Kuta, West Java, amid social and cultural changes. This research utilized a communication ethnography framework and Dell Hymes's SPEAKING paradigm (Setting, Participants, Ends, Act sequence, Key, Instrumentalities, Norms, Genre). It was conducted through participant observation, in-depth interviews with traditional leaders and residents, and document analysis of customary rules and ecotourism policies. The findings indicate that pamali remains an effective mechanism for forest conservation; however, younger generations increasingly interpret it through ecological and scientific perspectives rather than mystical or magical ones.. This shift shows that traditional taboos can evolve to remain relevant in the modern world, even whenchallenged by technology and tourism. The research enhances both academic discourse and practical application by demonstrating that traditional communication serves not only as cultural heritage but also as an effective ecological and social strategy that promotes community sustainability.